Implementasi Prinsip Utama Good Governance pada Penyusunan Laporan Kinerja Instansi Pemerintah di Bapperida Kabupaten Sragen - Rismauli Widya Ningtyas; Ida Setya Dwi Jayanti (JURNAL ADMINISTRASI KANTOR, 2025)
This research aims to analyze the implementation of the core principles of good governance in the process of preparing the Government Agency Performance Report (LKjIP) at the Regional Development Planning, Research, and Innovation Agency (BAPPERIDA) of Sragen Regency. The principles of good governance examined in this study include accountability, transparency, openness, and the rule of law. This research employs a qualitative method, with data collected through interviews, observations, and documentation. The informants in this study were members of the Planning, Evaluation, and Reporting Team (PEP) WorkingTeam of BAPPERIDA Sragen. The results show that BAPPERIDA Sragen Regency has implemented these principles in the preparation of the LKjIP. Although there are challenges related to the limited capacity of human resources, these constraints do not significantly affect the overall quality of the performance report produced. Keywords: Good Governance, LKjIP, Accountability, Transparency, Openness, Rule of Law